VDR gene TaqI (rs731236) polymorphism affects gut microbiota diversity and composition in a Caucasian population - Gonzalez-Soltero, Rocío; Tabone, Mariangela; Larrosa, Mar; Bailen, Maria; Bressa, Carlo (Frontiers in Nutrition, 2024)
Background: The VDR gene is identified as a crucial host factor, influencing the gut microbiota. The current research focuses on an observational study that compares gut microbiota composition among individuals with different VDR gene TaqI polymorphisms in a Caucasian Spanish population. This study aims to elucidate the interplay between genetic variations in the VDR gene and the gut microbial composition.Methods: 87 healthy participants (57 men, 30 women), aged 18 to 48 years, were examined. Anthropometric measures, body composition, and dietary habits were assessed. VDR gene polymorphism TaqI rs731236 was determined using TaqMan assays. The V3 and V4 regions of the 16S rRNA gene were sequenced to study bacterial composition, which was analyzed using QIIME2, DADA2 plugin, and PICRUSt2. Statistical analyses included tests for normal distribution, alpha/beta diversity, ADONIS, LEfSe, and DESeq2, with established significance thresholds.Results: No significant differences in body composition or dietary habits were observed based on VDR genotypes. Dietary intake analysis revealed no variations in energy, macronutrients, or fiber among the different VDR genotypes. Fecal microbiota analysis indicated significant differences in alpha diversity as measured by Faith's Phylogenetic Diversity index. Differential abundance analysis identified taxonomic disparities, notably in the genera Parabacteroides and Butyricimonas.Conclusions: Overall, this study suggests potential associations between genetic variations in the VDR gene and the composition and function of gut microbiota.